KESADARAN METAKOGNITIF MAHASISWA PROGRAM STUDI PENDIDIKAN FISIKA FKIP UNIVERSITAS JAMBI - Hidayat, M; Lestari, Neneng (EduFisika: Jurnal Pendidikan Fisika, 2019)
This study aims to knowthe metacognitive awareness of FKIP Physics Education Study Program students at Jambi University. The sample used was a total sample sample technique with 105 students. Metacognitive awareness was measured using Metacognitive Awareness Inventory (MAI) with a set of metacognitive sustainability indicators related to declarative knowledge, procedural knowledge, conditional knowledge, planning, information management strategies, comprehensive monitoring, debugging strategies and evaluating. The total number of questionnaire items was 52 items and data were analyzed using descriptive statistics. The most dominant indicators with very good categories are procedural knowledge (54.28%) and conditional knowledge (73.14%), planning (73.3%), understanding of monitoring (67.61%), improvement strategies (77, 77%) and evaluation (60%). Meanwhile the indicator of the strategy of managing information in the good category was 39.04% and very good at 40% and the declarative knowledge indicator in the good category was 43.8%..